Low‐temperature stiffening of air plasma‐sprayed 7 wt% Y2O3‐stabilized ZrO2. Issue 3 (26th November 2019) - Lal, Devi; Kumar, Praveen; Sampath, Sanjay; Jayaram, Vikram
Abstract: Evolution in bending modulus and accompanying microstructure of free‐standing air plasma‐sprayed Y2 O3 ‐stabilized ZrO2 subjected to thermal exposure, from 800°C to 1300°C, has been studied. The bending modulus was measured using custom‐made miniaturized cantilevers, which was loaded using a nanoindenter. Variation in the bending modulus was compared with the density change. The coating shows two domains of behavior of modulus variation with density: the low temperature/time domain wherein the bending modulus doubles without measurable change in the density and the high‐temperature domain where modulus increases monotonically with density. Finite element (FE) analysis was carried out using cross‐sectional micrographs of coatings to measure the elastic modulus of the actual coating and compared with experimentally observed values. The modulus values predicted by FE analysis are 70%‐80% higher than the experimentally observed values. An analytical model has been proposed to corelate the microcracks density and elastic modulus, which is in reasonable agreement with the experimentally measured values.